Heat and Mass Transfer On MHD Flow Problems with Hall and Ion Slip Effects On Exponentially Accelerated Plate - Pratapa, Kamala; Sheri, Siva Reddy (International Journal of Integrated Engineering, 2023)
We in this paper intended to investigate heat and mass transfer for MHD free convective flow for exponentially accelerated plate. The effects of Ion slip and Hall are studied considering variable temperatures, concentration, and angle of inclination. We applied finite element analysis for solving governing equations. Flow velocity, concentration and temperature’s graphical profiles are examined for non-dimensional parameters. Flow reversal is prevented due to magnetic field, is observed. Velocity experiences retarding effect due to angle of inclination, this helps in acknowledging drag force in seepage flow.